Navigating the Legal Minefield: The Impact of Articles 27A and 27B of Indonesia's EIT Law on Freedom of Expression and the Path to Legal Reform - Feka, Mikhael; Pujiyono; Sularto, R.B.; Pareke, JT. (Journal of Law and Legal Reform, 2025)
President Joko Widodo (Jokowi) officially approved the second revision of Law Number 1 of 2024 on the Second Amendment to Law Number 11 of 2008 on Electronic Information and Transactions (EIT) on January 4, 2024, reflecting the government's effort to align regulations with the rapid development of information and communication technology. While this revision introduces significant changes, particularly Articles 27A and 27B regulate actions that attack a person's honor or reputation. The public views it as a missed opportunity to eliminate existing ambiguities and potential misuse. This research employs normative legal methods with statutory, conceptual and comparative approaches, adopting a descriptive-prescriptive nature. The analysis reveals that the unclear definitions and potential for multiple interpretations of Articles 27A and 27B negatively impact freedom of expression, creating fear and uncertainty among the public, journalists, and government critics. Furthermore, these provisions violate fundamental human rights principles and contradict the 1945 Constitution and the values of Pancasila, which uphold freedom of expression and social justice. Therefore, while this revision reflects an effort to address the challenges of the digital era, further revisions are necessary to ensure that the law not only meets the needs of law enforcement but also protects human rights, freedom of expression, and remains consistent with the 1945 Constitution and Pancasila. This will prevent the law from becoming a tool for suppressing critical voices and journalistic investigations, which are essential to a healthy democratic society.